Effect of Health Education on The Enhancement Knowledge of First Trimester Primigravida about Discomfort and Management at Tamansari Health Center - Meti Patimah; Sri Susilawati; Sri Wahyuni Sundari (JURNAL KEBIDANAN, 2021)
During the pregnancy period there are physical and psychological changes and social changes become an experience for pregnant women, one of which is anxiety during pregnancy, the prevalence of anxiety disorders during pregnancy in Indonesia ranges from 28.7%. Factors that influence anxiety are knowledge, age, education, parity and social support. This research is to find out the effect of health education on discomfort in pregnancy trimester I and its handling of the knowledge of primigravida pregnant women first trimester. This research is an analytical study using a pre test post test design without control approach. The study subjects as many as 30 pregnant women in Karanganyar public health center using purposive sampling. Bivariate data analysis using paired t test. The results of the study obtained knowledge of pregnant women before health education amounted to 93.3% on the criteria less. Maternity knowledge after health education by 70% on the criteria is sufficient with a 29.4%  increase in knowledge with a p value of 0.000 α (0.05). This suggests that there is an influence of health education on discomfort in trimester I pregnancy and its handling of pregnant women's knowledge of trimester I primigravida